Investigating the efficacy of sodium hypochlorite, calcium hypochlorite and peracetic acid on environmental Escherichia coli strains - Bester, Carmen (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.